Determinant Analysis Of Conflict On Project Results In Aceh Province - Rinaldy, Rinaldy; Ikhsan, Muhammad (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The project is an activity with a target that must be completed within a certain period, where in its implementation often obstacles arise between the elements involved in it. Problems that arise must be immediately handled properly and appropriately so that the achievement of results is as expected.. Conflict is a condition of the oc-currence of discrepancies between values or goals to be achieved, both existing in individuals and in relationships with others. The purpose of this research is to find out one of the main factors causing conflict in project implementation. The method used in this study is a combined method, namely quantitative and qualitative methods through the distribution of questionnaires with the limitation of project observations from 2009-2011 that have been completed, with funding coming from the Aceh Budget (APBA). Designation of respondents for all classifications of construction services, from medium classification (M) to large classification (B). Population Construction executing services from the data obtained were 502 contractors, using the Slovin formula found a sample of 84 contractors. The independent variables reviewed are the owner factor and the project condition factor, while the dependent variable is the success of the project. To analyze data using multiple linear regression with the help of Product Solutions and Statistical Services (SPSS) version 22, while the statistical analysis performed in data processing is to test the validity and reliability. Based on research shows that the owner factor is one of the maint factors that cause conflict in project implementation in Aceh Province.